Utilization of Digital Technology in Employer Branding as a Recruitment Strategy at PT Victory International Futures: Pemanfaatan Teknologi Digital dalam Employer Branding Sebagai Strategi Rekrutmen di PT Victory International Futures - Nasywa Salsabila; Hery Pudjoprastyono (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
This study examines the utilization of digital technology in PT Victory International Futures' employer branding strategy to increase recruitment, specifically targeting the Millennial Generation and Generation Z. By adopting a qualitative case study methodology, this study analyzes the implementation of digitalization in the recruitment process. The results showed a 50% increase in digital interactions within two weeks after the first content was released through social media such as Instagram, X, and WhatsApp. Active online interactions, including direct messages and comments, successfully built two-way communication and increased candidate interest. In addition, the socialization of career opportunities through webinars has improved participants' understanding of the company's culture and opportunities. Nonetheless, challenges such as a lack of technical expertise in optimizing social media algorithms and content consistency remain. The study concludes that the integration of digital technology not only improves recruitment efficiency and expands candidate outreach but also builds a modern and adaptive corporate image, and has the potential to foster long-term employee loyalty.